USING VIEWING TECHNIQUE: ITS EFFECT ON STUDENTS’ VOCABULARY MASTERY ACCROSS LEARNING STYLE - ., Zulhirawati; Roza, Veni (STAI Bani Saleh, 2024)
There were some studies using video in teaching English recently. The research is used to find out the effect of using video in teaching English on students’ vocabulary mastery across learning style. The research involved 36 students from two classes at the second grade of Senior High School. The students were divided into class experiment and class control. The students in the experiment class were taught vocabulary by using video, and the students in control class were taught vocabulary by using book as media. The students in experiment and control class were further group according to their learning style (kinesthetic, audio and visual learner). The result of the study indicated that there was improvement of students’ vocabulary mastery and the result also described that there was an interaction between learning style and vocabulary mastery